Wintering strategies and breeding success: hypothesis for a trade-off in some waterfowl species - Tamisier, Alain; Allouche, Laurent; Aubry, François; Dehorter, Olivier (Wildfowl, 1995)
The dependence of the breeding performance of Anatidae on the body condition of birds (stored fat and protein) at the end of the winter season often has been reported. Several behavioural and ecological mechanism observed on three species of waterfowl at different periods of the winter season in the Camargue, south France, are interactive. They are integrated in a model of wintering strategy where birds optimise daily allocation of time and energy at all stages during the wintering period in order to be in 'pole position' throughout the season for access to food. Thus, body condition of birds at the beginning of the winter season can control body condition at the end of the season. We hypothesise the existence of a trade-off between wintering strategies and breeding success in that allocation of time and energy during winter can be adapted for better fitness. We predict that, at a specific level, the heaviest and/or the first birds to arrive at the winter quarter are the first to pair and have the best reproductive success during the following breeding season. Other cross-seasonal interactions are also suggested between breeding success and body condition during the following winter season.